Crisis financiera internacional: enfoque en instrumentos y riesgos - Palomino Selem, Carlos (2011)
The financial crises 2008 was very different respect to others financial crises because in this the market capitals had financial instruments very sophisticated that had two characteristic: one side, permitted debt structuring through which the debt instruments was segmented in capital and interest, that allowed risk diversification and low it. Other side, the agreements included embedded “insurances” known like CDS (credit default swap) which are exchange annuity payments that supported in case the debt fall in default. This scheme into of a context of globalization potentiated and deepened the crises.